Your voices fill the void in my mind. - Tan, Peiling. (2010)
“Your Voices Fill The Void In My Mind”, is a multimedia installation derived from an interest in examining how auditory memories are remembered and its effect on visual imagination during the recollection. By attempting to find out how voice memories help in visual recall, I asked my family members to recall individual voices of one another and the visual imageries that were brought about during the voice recollection. These images and voices were then recorded and re-interpreted into the installation piece, projected into a custom space. In the installation set-up, the projectors are specifically made to project images based on specified time intervals.